Development of STEM - Project Based Learning Devices to Train 4C Skills of Students - Kurniahtunnisa, Kurniahtunnisa; Wowor, Ester Caroline (Bioeduca : Journal of Biology Education, 2023)
The study aims to describe the validity, applicability, and effectiveness of the developed learning aids. This research is a research and development (R&D) research that uses the Borg and Gall model. The subjects of the wide-scale trial were 106 students of class XI at SMAN 16 Semarang. The data analysis used was descriptive percentages.  The results and conclusions of this study indicate that: (1) overall learning aids are highly valid based on expert validation, and construct validity, especially for tests of critical thinking skills obtained valid and reliable results (2) learning aids are well implemented; (3) learning aids effectively improve students' critical thinking skills with >75% of students meeting the minimum completion criteria, and regarding N-gain test, there is an increase in critical thinking skills with moderate criteria.  The STEM-PjBL Learning aids effectively trains the ability to think creatively, communicatively and collaboratively with high criteria.